PREVALENCE OF CHILDHOOD SKIN DISORDERS ATTENDING AT OUTPATIENT PEDIATRIC HOSPITAL - THUMMANAPALLY, NANDINI; LAWDYAVATH, KAVITHA; GURUVA, CHARANDAS; ENUMULA, DEEPTHI; PVK, SASTRY; ANCHURI, SHYAM SUNDER (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to study the prevalence of various skin diseases in pediatric population. Methods: A prospective observational study was conducted at private children’s outpatient clinic in Warangal from March to August 2018 with the prior approval from the Institutional Ethical Committee BIPS/IEC/2018/P8. A total of 200 patients with various skin diseases of age group <17 years were included in the study. Results: Out of 200 pediatric skin disorders, male children 138 (69%) outnumbered female children 62 (31%). The mean age of the study population was found to be 5.85±4.11 years. About 64% of the patients are from rural area and 36% are from urban. The percentage of skin disorders is allergic infections (26%), bacterial infections (23%), viral infections (11%), fungal infections (7.5%), parasitic infections (6%), autoimmune disorders (4%), and skin adnexa (2.5%). Conclusion: Our study concludes that the prevalence of allergic and bacterial skin infections was found to be common among male children from rural area